2018
DOI: 10.1002/cncr.31247
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in the risk of second primary cancers among survivors of adult‐onset cancers, 1980 through 2013: An Australian population‐based study

Abstract: In Tasmania, the risk of SPCs among survivors of adult-onset cancers has increased with periods of first cancer diagnosis from 1980 through 2009. Increased cancer screening and improved medical imaging may have contributed to the greater risk in recent years. Cancer 2018;124:1808-18. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…We observed that patients with EC-LUSC and EC-LUAD were more often diagnosed in recent years (2010 to 2016) compared to patients with LC-1.These results might be attributed to the improvement of diagnostic technique over time and shorter follow-up intervals of EC patients. In fact, some researches con rmed that cancer survivors received more frequent screening for various subsequent primary cancers than patients without a history of cancer [22][23][24]. The fact that cancer survivors might receive better surveillance for new cancers also explained why individuals with previous EC tended to diagnosed at an earlier stage compared with LC-1 individuals in this study, which was consistent with previous study [25].…”
Section: Patient and Tumor Characteristicssupporting
confidence: 91%
“…We observed that patients with EC-LUSC and EC-LUAD were more often diagnosed in recent years (2010 to 2016) compared to patients with LC-1.These results might be attributed to the improvement of diagnostic technique over time and shorter follow-up intervals of EC patients. In fact, some researches con rmed that cancer survivors received more frequent screening for various subsequent primary cancers than patients without a history of cancer [22][23][24]. The fact that cancer survivors might receive better surveillance for new cancers also explained why individuals with previous EC tended to diagnosed at an earlier stage compared with LC-1 individuals in this study, which was consistent with previous study [25].…”
Section: Patient and Tumor Characteristicssupporting
confidence: 91%
“…As our study cohorts were retrospectively collected within a long period, it is likely the risk of SPC was influenced by the secular trends of anticancer therapies. Improved screening and treatment strategies may have greatly prolonged patients' survival and thus lead to higher risk of exposure to a subsequent cancer [38]. Besides, the validity of our proposed nomogram needs further exploration in other population-based datasets.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of patients are surviving from cancer because of the increased survival as well as the advances in cancer screening programs and novel treatments [ 1 3 ]. However, all cancer survivors are at risk for developing a second primary cancer [ 4 6 ]. It was reported that the incidence of second malignant neoplasm (SMN), calculated from the Surveillance, Epidemiology, and End Results (SEER) Program, was approximately 8.1% between 1992 and 2008 in the United States, indicating that nearly 1 in 12 cancer patients can develop a SMN [ 6 ].…”
Section: Introductionmentioning
confidence: 99%